2020
DOI: 10.21203/rs.3.rs-40401/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Invastigation of persica mouth wash versus doxepin 0.5% oral rinse for chemo-radiotherapy-induced mucositis pain in the treatment of head and neck cancers, a randomized double blind clinical trial

Abstract: Abstract Background: One of the common side effects of radiotherapy and chemotherapy in patients with head and neck cancer is oral mucositis. This painful complication restricts the ability to eat and drink and increases the risk of oral infections. The aim of this study was to investigate the effect of doxepin oral rinse 0.5% in comparison with persica mouthwash on reducing the pain of oral mucositis in patients with head and neck cancer after radiotherapy and chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It is very important to use drugs other than painkillers and anti-in ammatory steroids with similar and even better effects with fewer side effects. Many studies have been conducted to investigate the effect of oral doxepin on pain, which has shown the reduction of pain with the use of this drug in various diseases [30][31][32]. It has been suggested in studies that TCA drugs such as doxepin, when used topically, can show analgesic effects with different mechanisms, including local anesthetic effects and central effects [23].…”
Section: Discussionmentioning
confidence: 99%
“…It is very important to use drugs other than painkillers and anti-in ammatory steroids with similar and even better effects with fewer side effects. Many studies have been conducted to investigate the effect of oral doxepin on pain, which has shown the reduction of pain with the use of this drug in various diseases [30][31][32]. It has been suggested in studies that TCA drugs such as doxepin, when used topically, can show analgesic effects with different mechanisms, including local anesthetic effects and central effects [23].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the most effective mechanical way to clean plaque is tooth brushing 7 . One alternative in brushing teeth is using miswak 18 .…”
Section: Characteristicmentioning
confidence: 99%
“…One alternative in brushing teeth that is usually used by Muslims is miswak. Miswak is a plant from the Salvadoraceae family 7 . Several previous studies have reported the presence of antibacterial substances in miswak against cariogenic bacteria and periodontal pathogens, especially Bacterioides species [8,9].…”
Section: Introductionmentioning
confidence: 99%